Effective wound management and wellbeing: guidance for clinicians, organisations and industry - Gray, D.; Boyd, J.; Carville, Keryln; Charles, H.; Lindholm, C.; Macdonald, J.; Mudge, E.; Price, P.; White, W. (Wounds UK, 2011)
A meeting was held at the Wounds International Conference in Cape Town on 1 February 2011 with the goal of gathering information on how patient wellbeing could be optimised by clinicians, healthcare organisations and industry while providing wound management. The meeting was attended by healthcare professionals from USA, Europe and Australia. It was identified that patient wellbeing and the impact of a wound concerned far wider issues than just pain, the main focus of much of the literature on patient quality of life (QoL). Achieving optimal wellbeing in patients with wounds requires a coordinated approach with a significant responsibility resting with the clinician (Figure 1).The resultant consensus document aims to provide guidance to clinicians, organisations and industry on how to provide wound care that optimises patient wellbeing.